Learnability Advantage of Segmental Repetitions in Word Learning - Basnak, Johanna; Ota, Mitsuhiko (Language and speech, 2024)
To date, research on wordform learning biases has mostly focused on language-dependent factors, such as the phonotactics and neighborhood density of the language(s) known by the learner. Domain-general biases, by contrast, have received little attention. In this study, we focus on one such bias—an advantage for string-internal repetitions—and examine its effects on wordform learning. Importantly, we consider whether any type of segmental repetition is equally beneficial for word recall, or whether learning is favored more or only by repeated consonants, in line with previous research indicating that consonants play a larger role than vowels in lexical processing. In Experiment 1, adult English speakers learned artificial consonant-vowel-consonant-vowel words containing either a repeated consonant (e.g., /sesu/, “c-rep”), a repeated vowel (e.g., /sepe/, “v-rep”), or dissimilar consonants and vowels (e.g., /sepu/, “no-rep”). Recall results showed no advantage for v-reps but higher accuracy for c-reps compared with no-reps. In Experiment 2, participants performed a label preference task with the same stimuli. The results showed dispreference for both c-reps and v-reps relative to no-reps, indicating that the results of Experiment 1 are independent of wordlikeness effects. These outcomes reveal that there is a form-learning bias for words with identical consonants but not for words with identical vowels, suggesting that a domain-general advantage for repetitions within strings is modulated by a language-specific processing bias for consonants.